ANALISIS KEMAMPUAN LITERASI SAINS SISWA SMP KELAS VIII DI KOTA TARAKAN - Irma Alisha; Listiani Listiani; Vlorensius Vlorensius (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2021)
Abstract: This research is motivated by the low achievement of scientific literacy in Indonesia in the Program for International Student Assessment (PISA) study participation held every three years by the Organization for Economic Co-operation and Development (OECD). This study aims to determine the scientific literacy ability of Class VIII Junior High School students in Tarakan City, which was taken using the Purposive Sampling technique. The data was taken using a test method in the form of a description question. The test given was adopted from the PISA questions published by the National Assessment Program (NAP) published in 2009 and translated into Indonesian. The results showed that the Science Literacy Ability of Class VIII Junior High School Students in Tarakan City was categorized as less with a percentage of 44.04%. At each level, students can only answer questions with levels 1 and 2, while for questions with levels 3 and 4, they are still very lacking. So it was concluded that the scientific literacy skills of class VIII junior high school students in Tarakan City were still lacking. Keywords: scientific literacy, student, PISA